Tingkat pengetahuan mahasiswa profesi terhadap Pencegahan dan pengendalian infeksi tuberkulosis : Kajian pada RSGM-P FKG Universitas Trisakti (Laporan Penelitian) - Shafira Pertiwi; Tiarma Talenta Theresia (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Tuberculosis is a chronic granulomatous disease caused by Mycobacterium tuberculosis bacteria. Globally, tuberculosis still becomes a threat to public health, with approximately 11 million infected cases every year. Based on WHO in Global Tuberculosis Report 2020, Indonesia (8.5%) becomes the second-highest country after India (27%). As one of the health workers with a high risk of being infected with tuberculosis, dental students are important to have good knowledge about the prevention and control of tuberculosis infection as one attempt to prevent the risk of tuberculosis infection in dental practices. Objective: To find out an overview of dental students’ knowledge level towards the prevention and control of tuberculosis infection in Dental and Oral Hospital of the Faculty of Dentistry, Trisakti University. Method: This study was a descriptive observational research with a cross-sectional study approach and was conducted by distributing questionnaires to 92 dental students who entered the clinical clerkship in 2019 and 2020. Results: The results show that 42.39% of students have a high knowledge level, 28.26% have a moderate knowledge level, and 29.35% have a low knowledge level. Conclusion: In this study can be concluded that the knowledge level of dental students who entered the clinical clerkship in 2019 and 2020 is still inadequate.